2010
DOI: 10.1063/1.3464197
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot-array diffraction grating with single order diffraction property for soft x-ray region

Abstract: A gold transmission grating is used routinely to disperse the x-ray spectrum at the Z soft x-ray facility to measure the spectrum and temporal history of the absolute soft x-ray power emitted from z-pinch and hohlraum radiation sources. A quantum-dot-array diffraction grating (QDADG) of 250 lines/mm for soft x-ray is designed and fabricated for the first time according to the principle of binary sinusoidal transmission grating. The diffraction efficiencies of the grating are measured in the 150-300 eV photon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In 2001, Kipp et al [8] proposed a new zone plate, or photon sieve, with a large number of pinholes distributed appropriately over the Fresnel zones that focused soft x-rays to a sharp focal spot and suppressed higher orders. Other x-ray gratings that can suppress higher-order diffractions were developed, such as the binary sinusoidal transmission grating (BSTG), [9] the quantum-dot-array diffraction grating (QDADG), [10][11][12] and the quasi-sinusoidal single-order diffraction transmission grating (QSTG). [13] Unfortunately, the BSTG and the QDADG do not have line densities greater than 1000 lines/mm.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Kipp et al [8] proposed a new zone plate, or photon sieve, with a large number of pinholes distributed appropriately over the Fresnel zones that focused soft x-rays to a sharp focal spot and suppressed higher orders. Other x-ray gratings that can suppress higher-order diffractions were developed, such as the binary sinusoidal transmission grating (BSTG), [9] the quantum-dot-array diffraction grating (QDADG), [10][11][12] and the quasi-sinusoidal single-order diffraction transmission grating (QSTG). [13] Unfortunately, the BSTG and the QDADG do not have line densities greater than 1000 lines/mm.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the STG theory, Cao et al have proposed several types of binary sinusoidal transmission gratings [7][8][9][10][11][12][13][14][15] since 2007. All these binary sinusoidal gratings with nonharmonic diffraction are composed of lots of small size units or complicated structures.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report random position rectangle grating (RPRG) which is designed to overcome these disadvantages. The fabrication of RPRG is much easier than the binary sinusoidal gratings mentioned above [7][8][9][10][11][12][13][14][15] while the property of high-order diffraction restraint is kept. Its 1st-order theoretical absolute diffraction efficiency is as high as 4.1%, far above all binary sinusoidal transmission gratings.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, some binary single order diffraction gratings have been developed. [12][13][14][15][16][17][18][19][20][21] A quantum-dot-array diffraction grating (QDADG) has been reported by Wang et al, [12,13] and in its design a great many quantum dots are distributed on a substrate, which obey the sinusoidal function. A QDADG for visible light has been fabricated and the experiment has shown that higher-order diffractions disappear as predicted.…”
Section: Introductionmentioning
confidence: 99%